Adipocyte dysfunction promotes lung inflammation and aberrant repair: a potential target of COPD - Zhang, Si-jin; Qin, Xian-zheng; Zhou, Jie; He, Bin-feng; Shrestha, Surendra; Zhang, Jing; Hu, Wei-ping (Frontiers in Endocrinology, 2023)
Background: Obesity and Chronic obstructive pulmonary disease (COPD) are prevailing worldwide, bringing a heavy medical burden. Clinical and pathophysiological relationship between obesity and COPD are paradoxical and elusive. We aim to explore their inherent associations from clinical, genetic and animal levels.We performed literature review and cohort analysis of patients with COPD to compare lung function, symptom and prognosis among different weight groups. After retrieving datasets of obesity and COPD in GEO database, we carried out differentially-expressed gene analysis, functional enrichment, protein-protein interactions network and weighted gene co-expression network analysis. Then, acquired paraffin-embedded lung tissues of FABP4-Cre-BMPR2 fl/fl (CKO) mice which were characterized by adipocyte-specific knockout of BMPR2 for staining and analysis.Results: Our cohort study reports the effect of obesity on COPD to be inconsistent with previous clinical studies. Lung function of overweight group was statistically superior to that of other groups. We also found the inflammatory factors significantly increased hub genes, and cytokine-associated pathways were enriched in white adipose tissue of obese patients. Similarly, injury repair-associated genes and pathways were further enhanced in the small airways of COPD patients. CKO mice spontaneously developed lung injury, emphysema and pulmonary vascular remodeling, along with increased infiltration of macrophages. BMPR2-defiecient adipocytes had dysregulated expression of adipocytokines.Inflammation and abnormal repair might be potential mechanisms of the pathological association between obesity and COPD. BMPR2-associated adipocyte dysfunction promoted lung inflammation and aberrant repair, in which adipocytokines might play a role and thus, could be a promising therapeutic target.